The Essential Cubism 1907-1920 : Braque, Picasso & their friends - Cooper, Douglas; Tinterow, Gary (London : Tate Gallery, 1983)
Braque, Georges ; Gris, Juan ; Léger, Fernand ; Picasso, Pablo ; Laurens, Henri ; Liptchitz, Jacques ; Delaunay, Robert ; Marcoussis, Louis ; Metzinger, Jean ; Villon, Jacques ; etc.
The Essential Cubism 1907-1920 : Braque, Picasso & their friends, Tate Gallery, London, 27 April - 10 July 1983
boek